Practicality Practicality of Development of Jigsaw Type of Cooperative Model Learning Module in Scientific Work Screening courses and Seminars - Bulkia Rahim; Usmeldi Usmeldi; Arwizet Karudin (Jurnal Teknologi Informasi dan Pendidikan, 2021)
This research is concerned with the practicality of developing a jigsaw-type cooperative learning module in the course of writing scientific papers and seminars in the mechanical engineering department, Faculty of Engineering, Padang State University. The purpose of this study was to identify the practicality of developing a jigsaw-type cooperative learning module in the course of Scientific Writing and Seminar. The type of research used is quasi-experimental. The subjects of this study amounted to 67 levels 4 students in the course of Scientific Writing and Seminar. The type of data used is primary data which is distributed to expert lecturers and students. The data collection technique in this study was in the form of a questionnaire. Research data analysis techniques to describe the practicality of developing a jigsaw-type cooperative module for Scientific Writing and Seminar courses. Based on the results of the practicality test that was distributed to the lecturers, the lecturer response data were obtained with an assessment percentage of 97.50% in the "very practical" category while the results of the practicality test distributed to students obtained response data with an assessment percentage of 81.12% with the category " very practical.”